Pengaruh Nisbah C/N dalam Vermicomposting Campuran Ekskreta Ayam Petelur dan Serasah Dedaunan terhadap Perubahan Suhu, Jumlah Total Bakteri, dan Koliform - Muhammad Amien Hawari; Yuli Astuti Hidayati; Wowon Juanda (Unpad Press, 2022)
Concentrated layer poultry farm produce manure that accumulate in one place and have the potential to pollute the environment. Manure is an organic material that is not yet stable and contains both pathogenic and non-pathogenic microbes, therefore it needs to be handled so that the organic waste material decomposes into nutrients that are stable and safe for the environment. Manure can be processed by vermicomposting, one of the requirements for vermicomposting is a C/N ratio, manure has a low C/N ratio, to increase the substrate C/N ratio, leaf litter can be added. The purpose of the study is to know the effect of C/N ratio in vermicomposting of chicken excrement mixture and foliage on the temperature changes, total number of bacteria and coliform and on the C/N balance that produces the lowest total coliform. Research was conducted using a complete randomized design consists of 3 treatment with different ratio C/N, P1(C/N 25), P2(C/N30), P3(C/N 35) which is repeated 6 times, Data were analyzed with the variance and continued with Duncan Test. The results showed that the C/N ratio balance in vermicomposting of the mixture of manure and leaf litter had a significant effect on the total number of bacteria, but had no significant effect on total coliform. The balance of C/N ratio of 30 resulted in the highest total bacterial count and the lowest coliform in the decomposition process of 60.67 x 1011 cfu/g and 12,86 MPN/mL.